Effect of perceived organizational support and organizational trust on young academics’ organizational commitment - Atalay, Mustafa Ozgun; Birincioglu, Nihan; Acuner, Taner (Publishing House of Wroclaw University of Economics and Business, 2022)
The most important mission of universities is the production of highly skilled manpower and research outputs. In this context, the ability of universities to implement these missions is directly related to their human resources. Academics are the most important intellectual capital of universities, and the support they receive from the universities they work for plays a critical role in the realization of this objective. Organizational trust is also vital for successful relations and collaboration to share research and teaching ideas and address problems in universities. Both of these have an impact on their scientific activities, as well as motivation to work and commitment. Therefore, drawing on the social exchange theory, the aim of this study was to examine the effects of young academics’ perceived organizational support and organizational trust on their organizational commitment behaviour. The sample comprised 305 young academics in Turkey. This study showed that perceived organizational support and organizational trust have a significant and positive impact on affective and normative commitment. However, trust in managers has a significant and negative impact on continuance commitment.
Argumenta Oeconomica, 2022, Nr 1 (48), s. 201-233
Keywords: perceived organizational support; organizational trust; organizational commitment; social exchange theory; young academics